On The Maximal Ideals In The Banach Space Of Quasicontinuous Functions - Kumar, V. Srinivasa (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
In this paper, some interesting properties of QuasicontinuousÂ functions are presented.Â The maximal ideals in the Banach space of bounded real valuedÂ Quasicontinuous functions defined on [0,1] are investigated.